Prevalence and Clinical Characteristics of Itch in Vitiligo and Its Clinical Significance - Vachiramon, Vasanop (Biomed Res Int, 2017)
OBJECTIVE: Vitiligo usually presented as asymptomatic depigmented macules and patches. Little is known regarding itch in vitiligo. This study aimed to evaluate the prevalence and characteristics of itch in vitiligo patients. PATIENTS AND METHODS: A cross-sectional study was conducted on vitiligo patients. Itch character and intensity were determined through questionnaires. Evaluation was also made by dermatologists to define vitiligo subtype, body surface area, Koebner phenomenon (KP), and so on. Data were assessed by computer software. Results were considered statistically significant if p < 0.05. RESULTS: Among 402 patients, itch on vitiliginous lesion presented in 20.2%. Prevalence of itch was most common in focal vitiligo (29.4%), followed by segmental vitiligo (20.3%) and nonsegmental vitiligo (19.6%), respectively. Tingling sensation was the most common itch-related symptom (82.7%). The median itch intensity is 5 by 10-point visual analog scale. Daily activity and sleep disturbance were observed in 60.5% and 39.5% of patients who experience itch. Itch occurred approximately 3 days prior to the development of lesions in 48.1% of patients. Thirty-two patients (78.1%) with both itch and KP type IIb had active disease. CONCLUSIONS: Itch in vitiligo is not uncommon. The presence of itch with KP type IIb may warrant the active vitiligo.